(3GdWQGR GdePgH aj GdONjd hGdeYQHs - (3GdfgGdj , eMeO GdfgGdj GdMdHj,J (B1186 (3g` s
(3ChdgG (B:s
(3hHYO ajbhd GdabjQ dQHg GdZfi GdeJYGdi eMeO GdeOYh GdfgGdi deG GWdYJ Ydi eYQH CHj efUhQ GdLhGjbi s
(3BNQgG (B:s
(3hQLY Edi GdEMSGA s
(3fSNI eWHhYI SfI (B176(3es
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B81s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B82s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GddZIs